2019
DOI: 10.2147/prbm.s227403
|View full text |Cite
|
Sign up to set email alerts
|

<p>Imagination Matters When You Shop Online: The Moderating Role of Mental Simulation Between Materialism and Online Impulsive Buying</p>

Abstract: BackgroundSeveral studies have demonstrated that materialistic people tend to engage in impulsive buying. However, how to help them reduce such irrational behavior, especially in online shopping context, is not known. This study aimed to explore whether mental simulation moderates the relationship between materialism and online impulsive buying.MethodsA total of 200 Chinese college students participated in the experiment. We adopted an imaginary priming paradigm to manipulate three types of mental simulation: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In this way, it has been demonstrated that materialistic people tend to make compulsive purchases. However, there are protective factors of compulsive buying in materialistic people that could have influenced the results found [ 60 ]. For example, previous studies have highlighted that life satisfaction would act as a protective factor against compulsive buying in students [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, it has been demonstrated that materialistic people tend to make compulsive purchases. However, there are protective factors of compulsive buying in materialistic people that could have influenced the results found [ 60 ]. For example, previous studies have highlighted that life satisfaction would act as a protective factor against compulsive buying in students [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The important influence of downward anticipated regret on online impulsive buying behavior has been supported. Positive expectations on future results can enlarge the possibility of online impulsive buying (Li et al, 2019). When the direction of anticipated regret is upward, the future choice is better than the current choice.…”
Section: Discussionmentioning
confidence: 99%
“…Tom et al asserted that shopping online could lead consumers to impulse spending [39]. Impulsive spending behavior in social e-commerce has been studied by Xiang et al [40], Li et al [41], and Zafar et al [42]. They concluded that the mutual influence of friends promotes impulsive spending by consumers.…”
Section: A Influencer Marketing and Live-streaming Salesmentioning
confidence: 99%
“…This is because online influencers' promotion causes consumers to engage in hedonistic consumption. Using psychological experiments, Li et al [41] suggested ways to help consumers reduce and control impulse consumption.…”
Section: A Influencer Marketing and Live-streaming Salesmentioning
confidence: 99%